Agroforestry in India: Current scenario - Dhyani, S. K.; Handa, A. K. (Indian Farming, 2015)
Agroforestry plays a great role in maintaining the natural resource base and increases the productivity in the rainfed areas of arid and semi-arid regions. It also provides employment opportunities, carlon sequestration and farm productivity optimization. A lot more needs to be done to get more benefits of agroforestry, by filling up the gap in inadequate investment, extension strategies and market linkages.